870Methylation marks of prenatal exposure to maternal smoking and risk of cancer in adulthood. (2nd September 2021) - Dugué, Pierre-antoine; Hodge, Allison; Wong, Ee Ming; Joo, Eric; Jung, Chol-Hee; Hopper, John; English, Dallas; Giles, Graham; Milne, Roger; Southey, Melissa
Abstract: Background: Prenatal exposure to maternal smoking is detrimental to child health but its association with risk of cancer has seldom been investigated. Maternal smoking induces widespread and long-lasting DNA methylation changes, which we study here for association with risk of cancer in adulthood. Methods: Eight prospective case-control studies nested within the Melbourne Collaborative Cohort Study were used to assess associations between maternal-smoking-associated methylation marks in blood and risk of several cancers: breast (N = 406 cases), colorectal (N = 814), gastric (N = 166), kidney (N = 139), lung (N = 327), prostate (N = 847) and urothelial cancer (N = 404) and B-cell lymphoma (N = 426). We used conditional logistic regression models to estimate odds ratios (OR) and 95% confidence intervals (CI) for associations between cancer and five methylation scores calculated as weighted averages for 568, 19, 15, 28, and 17 CpG sites. Models were adjusted for confounders, including personal smoking history (smoking status, pack-years, age at starting and quitting), and methylation scores for personal smoking. Results: All methylation scores for maternal smoking were strongly positively associated with risk of urothelial cancer. Risk estimates were only slightly attenuated after adjustment for smoking history, other potential confounders and methylation scores for personal smoking. Potential inverse associations were observed with risk of lung cancer and B-cell lymphoma. Conclusions: We found that methylation marks of prenatal exposure to maternal smoking are associated with increased risk of urothelial cancer. Key messages: Our study demonstrates the potential for using DNA methylation to investigate the impact of early-life, unmeasured exposures on later-life cancer risk.